1970
DOI: 10.1088/0031-8949/2/4-5/010
|View full text |Cite
|
Sign up to set email alerts
|

Polarization in the Excitation of the 3-Level at 3.74 MeV in40Ca by 185 MeV Protons

Abstract: The polarization of 185 MeV protons inelastically scattered from the 3- level at 3.74 MeV in 40Ca has been measured in the angular region 10° to 42.5° (lab. system). The total energy resolution was 0.28 and 0.50 MeV (FWHM) for the two different targets used. The angular distribution obtained is in qualitative agreement with calculations performed in the distorted wave impulse approximation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 8 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Comparing the angular distribution for the polarization with the one obtained for the 3-level at 3.74 MeV in 40Ca [37] it is found that the shapes of the two distributions are very similar. In fact, they are almost identical when plotted versus the centreof-mass angle multiplied by as seen in Fig.…”
Section: The 275 Mevpeakmentioning
confidence: 68%
“…Comparing the angular distribution for the polarization with the one obtained for the 3-level at 3.74 MeV in 40Ca [37] it is found that the shapes of the two distributions are very similar. In fact, they are almost identical when plotted versus the centreof-mass angle multiplied by as seen in Fig.…”
Section: The 275 Mevpeakmentioning
confidence: 68%